2004
DOI: 10.4314/wsa.v27i1.5013
|View full text |Cite
|
Sign up to set email alerts
|

Plant-soil interactions of sludge-borne heavy metals and the effect on maize (<i>Zea mays</i> L.) seedling growth

Abstract: The use of sewage sludge as an organic fertiliser under South African conditions is an alternative disposal route to sacrificial land disposal. However, the lack of research done under South African conditions and the conservative nature of the heavy metal guidelines, when interpreted as total metal content is limiting the agricultural use of sludge. A glasshouse experiment, which forms part of a greater project, was conducted to characterise soil-plant interactions of the main sludge-borne heavy metals (Pb, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 8 publications
0
15
2
Order By: Relevance
“…pH and CaCO 3 values were determined between 7.6-7.85 and 2.52-2.58%, respectively. It is recommended that soil pH should be maintained above 6.5 for sludge-amended soils (Henning et al 2001). Smith (1994) noted that optimal pH value for growth of the majority of plants was between 6.5 and 7.0.…”
Section: Resultsmentioning
confidence: 99%
“…pH and CaCO 3 values were determined between 7.6-7.85 and 2.52-2.58%, respectively. It is recommended that soil pH should be maintained above 6.5 for sludge-amended soils (Henning et al 2001). Smith (1994) noted that optimal pH value for growth of the majority of plants was between 6.5 and 7.0.…”
Section: Resultsmentioning
confidence: 99%
“…Mobility could also have been enhanced by high hydraulic loading of approximately 4500 mm ha -1 yr -1 . A study conducted by Henning et al (2001) on a sludge-amended sandy soil showed higher Cd concentrations in control than sludge-mended soils due to Cd mobility. Kabata-Pendias and Andriano (1995) also reported trace metal mobility on acid sandy soils of low organic matter.…”
Section: Exchangeable Basesmentioning
confidence: 95%
“…Bray-1 P was extracted by Bray-1 method and determined as for total P. Exchangeable cations were extracted by acidified ammonium acetate followed by atomic absorption spectrophotometric determination for Ca and Mg, and flame emission for K and Na. Zn, Cu, Cr and Cd were extracted using the USEPA double acid digestion method which recovers almost 100% of the metals from the sample (Henning et al 2001). Samples were weighed, ashed and taken up in HClO 4 -HNO 3 solution and made up to a known volume.…”
Section: Soil Sampling and Analysismentioning
confidence: 99%
“…In order to evaluate metal translocation from the soil to the shoots, i.e., find out how much of the total metal concentration in the soil the plant actually took up and transferred to the shoots, an operationally defined transfer coefficient (TC), also known as transfer function (Adriano, 2001;Henning et al, 2001), was calculated. It is defined as the ratio of the metal concentration in the plant [M] plant to the total metal concentration in the soil [M] soil (Adriano, 2001;Henning et al, 2001).…”
Section: Metal Transfer Coefficientsmentioning
confidence: 99%